Understanding educators’ approaches to teaching mechanical systems and control in grade 8 - Msimango, Esie Zandile; Mtshali, Thokozani Isaac (Universitas Negeri Yogyakarta, 2025)
The quality of instruction in Mechanical Systems and Control significantly impacts learners’ grasp of technology concepts in Grade 8. The objectives of the research were: (1) to determine how Grade 8 educators applied pedagogical strategies to teach Mechanical Systems and Control, and (2) to assess the specific practices used in the classroom. Using a qualitative approach, data were collected through non-participant observations, semi-structured interviews and open-ended questionnaires conducted with seven (7) Technology educators across Madibeng schools. Data was transcribed and analysed using the 6 steps of thematic analysis. The findings revealed that while educators used a variety of teaching approaches such as demonstrations, practical tasks and learner-centred discussions, there was a lack of consistency between theory and practical application due to resource constraints and limited professional development. Educators expressed a preference for interactive and hands-on strategies; challenges such as large class sizes and time limitations were reported. The study recommended targeted training workshops and curriculum alignment to enhance teaching effectiveness. These findings contributed to a deeper understanding of pedagogical practices in Technology education. For further research, a mixed-method approach could provide a more comprehensive understanding by using learner performance data to evaluate the effectiveness of various teaching strategies.